Low rates of nitrogen and phosphorus as fertilizer options for maize (Zea mays L.) in drier regions - Kgonyane, Mailula Cedric (University of Limpopo (Turfloop Campus), 2010)
Refer to document.
Thesis (M.Sc. (Agronomy))--University of Limpopo, 2010
Keywords: Nitrogen; Phosphorus; Fertilizer; Maize; Dry regions; 633.15; Corn-Breeding -- South Africa